A Clinical and Histopathological study of Lichenoid Eruption of Skin in Two Tertiary Care Hospitals of Dhaka. - Khaled, A; Banu, SG; Kamal, M; Manzoor, J; Nasir, TA (Pulse, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/pulse.v5i1.20184 Pulse Vol.5 January 2011 p.12-18